2021
DOI: 10.1111/1745-9133.12557
|View full text |Cite
|
Sign up to set email alerts
|

Crime, quarantine, and the U.S. coronavirus pandemic

Abstract: Research Summary Priorresearch has produced varied results regarding the impact of the coronavirus pandemic on crime rates, depending on the offenses and time periods under investigation. The current study of weekly offense rates in large U.S. cities is based on a longer time period, a greater number of offenses than prior research, and a varying number of cities for each offense (max = 28, min = 13, md = 20). We find that weekly property crime and drug offense rates, averaged across the cities, fell during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…At present, it is not obvious what kind of violence has contributed to this drop, but a British study based on emergency room data, for example, found that the reduced violence was limited to violence outside the home, whereas violence at home did not wane ( Shepherd, Moore, Long, Mercer Kollar, & Sumner, 2021 ). Additionally, although early evidence has suggested that domestic violence might actually have increased during the lockdown ( Piquero, Jennings, Jemison, Kaukinen, & Knaul, 2021 ), other studies have not reached the same conclusion ( Lopez & Rosenfeld, 2021 ; Wang, Fung, & Weatherburn, 2021 ).…”
Section: Theorymentioning
confidence: 97%
“…At present, it is not obvious what kind of violence has contributed to this drop, but a British study based on emergency room data, for example, found that the reduced violence was limited to violence outside the home, whereas violence at home did not wane ( Shepherd, Moore, Long, Mercer Kollar, & Sumner, 2021 ). Additionally, although early evidence has suggested that domestic violence might actually have increased during the lockdown ( Piquero, Jennings, Jemison, Kaukinen, & Knaul, 2021 ), other studies have not reached the same conclusion ( Lopez & Rosenfeld, 2021 ; Wang, Fung, & Weatherburn, 2021 ).…”
Section: Theorymentioning
confidence: 97%
“…As restrictions were lifted, violent crime peaked during the summer and fall months. The authors argue that this finding lends support to routine activities/opportunity theory, as violent crime increased with greater levels of mobility of potential victims and offenders through time and space (Lopez & Rosenfeld, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 77%
“…In the United States, large scale shifts in routine activities brought on by social distance orders, school closures, and the closing of businesses, meant that more individuals were spending time at home, outside of the public sphere. Not surprisingly, these dramatic shifts in routines impacted crime and violence (Lopez & Rosenfeld, 2021). For mass shootings, however, the nature of this impact was unclear.…”
Section: Discussionmentioning
confidence: 99%